Transient Flow from a Partially Penetrating Well Installed in a Single Leaky Aquifer of Limited Thickness - Vashisht, A K; Shakya, S K (Journal of Agricultural Engineering, 2008)
A transient semi-analytical solution using integral transform techniques was developed to deal with well hydraulics of a draining/recharging partially penetrating well installed in a single leaky aquifer of limited thickness under ponded conditions. Flow equation is solved by incorporating Neumann type boundary conditions using Laplace transformation, Finite Fourier Cosine transformation, and modified Bessel functions. Applicability of the developed solution is shown using reasonable assumed data. Response of hydraulic head distribution with change in ponding heads was performed after selecting the suitable placement of the screen within the limited thick aquifer. Analyses showed that the well with screen placed in the centre of the isotropic aquifer was more efficient than well with screen positioned other than centre. It also revealed that the hydraulic head distribution was increasing with time and ponding depth. Developed solution was validated with the Hantush’s standard solution.